Enhancing Teacher Organizational Citizenship Behavior in Junior High School of Depok City - Lestari, Iis Dewi; Hardhienata, Soewarto; Sunaryo, Widodo (PPSDP International Journal of Education, 2024)
Teachers play a crucial role as agents of learning who can enhance the quality of education. Here are several issues regarding teachers’ Organizational Citizenship Behavior that have not yet met expectations, making it a suitable subject for research to explore the efforts needed to enhance Organizational Citizenship Behavior among teachers at State Junior High Schools in Depok City. The aim this research is to identify the factors that can enhance teachers’ OCB in public junior high schools in Depok City. The method of this research is used in this study is descriptive qualitative. In the data collection process, we employed methods such as interviews, observations, focus group discussions, and documentation. Interviews were conducted with 22 teachers from 3 public junior high schools in Depok City. We carried out observations accompanied by notes as part of the documentation and observation studies to identify factors that can enhance teachers’ OCB behavior. The object of this research is teachers’ OCB behavior, while the subjects of the study are teachers from public junior high schools in Depok City. How To enhance teachers’ OCB (Organizational Citizenship Behavior)? The result is for improvement of OCB behavior among teachers at SMP Negeri Kota Depok can be influenced by two variables: team work and spiritual belief. The novelty of this research was found two variables to enhance the OCB. There are team work and spiritual. Contribution my research for the study is find new method to enhance OCB because the variable found in the field.